Komparatif karakteristik demografis dan produktivitas pegawai kantor pelayanan pajak pratama samarinda - Arbarudinsyah Arbarudinsyah; Djoko Setyadi; Asnawati Asnawati (Faculty of Economics and Business Mulawarman University, 2016)
The conclusion of this study, there was no difference in employee productivity Tax Office Primary Samarinda visit of age employees Tax Office Primary Samarinda. There was no difference in employee productivity Tax Office Primary Samarinda visit of gender employees Tax Office Primary Samarinda. There was no difference in employee productivity Tax Office Primary Samarinda visit of the marital status of employees of the Tax Office Primary Samarinda. There was no difference in employee productivity Tax Office Primary Samarinda visit of employee education level Tax Office Primary Samarinda.Keywords: Demographic Characteristics and Productivity